The Self-Assembling Peptide P11-4 Prevents Collagen Proteolysis in Dentin. (March 2019) - de Sousa, J.P.; Carvalho, R.G.; Barbosa-Martins, L.F.; Torquato, R.J.S.; Mugnol, K.C.U.; Nascimento, F.D.; Tersariol, I.L.S.; Puppin-Rontani, R.M.
The major goal in restorative dentistry is to develop a true regenerative approach that fully recovers hydroxyapatite crystals within the caries lesion. Recently, a rationally designed self-assembling peptide P11 -4 (Ace-QQRFEWEFEQQ-NH2 ) has been developed to enhance remineralization on initial caries lesions, yet its applicability on dentin tissues remains unclear. Thus, the present study investigated the interaction of P11 -4 with the organic dentin components as well as the effect of P11 -4 on the proteolytic activity, mechanical properties of the bonding interface, and nanoleakage evaluation to artificial caries-affected dentin. Surface plasmon resonance and atomic force microscopy indicated that P11 -4 binds to collagen type I fibers, increasing their width from 214 ± 4 nm to 308 ± 5 nm ( P < 0.0001). P11 -4 also increased the resistance of collagen type I fibers against the proteolytic activity of collagenases. The immediate treatment of artificial caries-affected dentin with P11 -4 enhanced the microtensile bonding strength of the bonding interface ( P < 0.0001), reaching values close to sound dentin and decreasing the proteolytic activity at the hybrid layer; however, such effects decreased after 6 mo of water storage ( P < 0.05). In conclusion, P11 -4 interacts with collagen type I, increasing the resistance of collagen fibers to proteolysis, and improves stability of the hybrid layer formed by artificial caries-affected dentin.